Small nomadic peoples, Berendei tribe, Chornye Klobuki (Black Hats) and Bierladnicy Tribe vs. Kievan Rus (Ruthenia) - Kijas, Artur (Balcanica Posnaniensia. Acta et studia, 2007)
The article concerns the relations between small nomadic peoples – the Berendeys, Black Khlobuks, and Berladniks – and Kievan Rus' in the 11th–12th centuries. The aim is to show the mechanisms of cooperation and rivalry, as well as the impact of these contacts on socio-cultural changes. The source material consists of 12th-century Rus chronicles, supplemented by linguistic and toponymic analyses and archaeological findings. The author's conclusions indicate that the Berendeys, initially typical nomads, gradually adopted a semi-sedentary lifestyle thanks to long-term settlement along the Dnieper, creating strongholds and a social structure similar to that of the Rus. As part of the Black Klobuks federation, they actively participated in dynastic struggles and rivalries between the princes of Kiev and the Polovtsians. The Black Klobuks, perceived in sources as a relatively independent political force, skillfully balanced between dependence on Kievan Rus and their own interests. The Berladians, concentrated around the center on the lower Seret River, were a multi-ethnic community living off raids and plunder. They were considered the precursors of the later Cossack movement.